SEX DIFFERENCES IN REFLECTIVE PROCESSESS AMONG POLICE OFFICERS - Четверик-Бурчак, Аліна Григорівна; Шаповал, Тетяна Юріївна (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2020)
The article presents the results of the theoretical and methodological substantiation and empirical verification of the approach to investigation sex differences in representation of reflection among police officers. The object of study is reflection. The research deals with sex differences in reflective processess among police officers. Positive (systemic reflection, self-regulation, meaning-in-life) and negative (quasi-reflection, introspection) varieties of the phenomenon are analyzed. Eighty participants (40 male and 40 female) aged from 20 to 45 years reported in a survey their own level of reflection, self-regulation, self-attitude and meaning-in-life. The research revealed that the female and male groups of police officers differ on the variables of systemic reflection, quasi-reflection, introspection, activity reflection, self-regulation, self-attitude, reflectivity and meaningfulness of life. Female police officers prone to report higher level of reflection (systemic reflection as well as quasi-reflection and introspection) comparing to male representatives. Activity reflection of women is focused on the process, while men tend to concentrate on the result. The original research hypothesis was confirmed and the findings demonstrate that there are sex differences in reflective processes among police officers. The practical value of the work lies in the explanation of sex differences in reflective processes among police officers. The findings open up new prospects in application of the results in psychodiagnostics, preventive and corrective interventions to assist police officers, in the field of psychological counseling and training